The Inhibition of 15-Lipoxygenase by Blechnum orientale Leaves and its Glycoside-flavonoid Isolates: In Vitro and In Silico Studies - Rissyelly Rissyelly; Syaikhul Aziz; Frangky Sangande; Agung Wibawa Mahatva Yodha; Krisyanti Budipramana; Elfahmi Elfahmi; Sukrasno Sukrasno (Bogor Agricultural University, Indonesia, 2022)
Fern is one of the groups of primitive plants rich in secondary metabolites that are commonly used to treat various diseases, including antioxidant, anti-hyaluronidase, anti-inflammation, and respiratory disease but less investigated. Flavonoid is one of the secondary metabolites abundantly present in ferns. This study aims to isolate major compounds found in Blechnum orientale act as 15-lipoxygenase (15-LOX) inhibitors. Inhibition of lipoxygenase decrease the production of leukotriene that induces bronchoconstriction in asthma. Isoquercitrin (Quercetin-3-O-β-glucopyranoside) and trifolin (kaempferol-3-O-β-D-galactoside) have been successfully isolated from Blechnum orientale. Further in silico study was performed to explain the binding mode between flavonoid pyranoside or galactoside and flavonoid aglycone in the 15-LOX cavity and their amino acid residues interaction. Isoquercitrin binds with Ile663, Ile400, Leu408, Leu597, Ala404, and Arg403 in the 15-LOX cavity as a lipoxygenase inhibitor. Trifolin binds the same amino acids as isoquercetin with addition His366, Gln596, and Phe175. Both isoquercitrin and trifolin act as competitive inhibitors against lipoxygenase enzymes.